Political Stability and Economic Growth Across Democratic Regime Types: Evidence from 38 OECD Countries (Third Sector Social Economic Review, 2025)
Political stability/instability, which has become one of the striking elements with the use of institutional factors in explaining the economic performance of countries, has become a subject of more research in the economic literature in recent years. Studies reveal that political stability, an important part of institutional economics, may shape a number of factors that directly or indirectly affect economic performance. The relationship between political stability/instability and economic growth, which can be seen in different types of political regimes from democratic to autocratic regimes, has been discussed limitedly in the literature. However, factors such as the structure of democratic institutions, quality of governance, decision-making processes and legal stability can vary significantly depending on the regime type. In this context, this study aims to examine the relationship between political stability and economic growth in the context of different political regime types. For this purpose, 38 OECD countries were divided into three subgroups according to the types of political regimes they implemented: liberal democracy, electoral democracy and closed autocracy. Panel cointegration test and CS-ARDL model were used in the analysis of the study covering the period 2000-2022. According to the results of the study, the effect of political stability on economic growth is positive in liberal and electoral democracies, while it is negative in closed autocracies. The findings reveal that the effect of political stability on economic growth varies according to regime type and offer important implications for policy makers.
Keywords: Politic Stability; Economic Growth; Politic Regime Types; CS-ARDL; OECD